REGULATORY NUCLEIC ACID MOLECULES FOR ENHANCING GENE EXPRESSION IN PLANTS - MEULEWAETER, Frank; LISERON-MONFILS, Christophe (2025)
The current disclosure generally relates to the technical field of plant molecular biology and provides methods for the production of high expressing promoters and the production of plants with enhanced expression of nucleic acids wherein combinations of at least two nucleic acid expression enhancing nucleic acids (NEENAs) are functionally linked to said promoters and/or introduced into plants.